An analysis of PBSI students' ability and component levels of narrative texts - Dewi, Rishe Purnama; Krismawati, Septina (Jurnal Pendidikan Bahasa Indonesia, 2022)
This research was structured with two objectives, the first, to describe the ability to write personal narrative essays of PBSI USD students with Storybird media.Â  Second, describe what components of narrative writing need to be improved in Creative Writing lectures. This research is included in quantitative descriptive research. The population in this study were sixty-nine PBSI USD students who took the Creative Writing course. The source of the data in this study is the result of a narrative essay made by the sixty-nine PBSI USD students who took the Creative Writing course. To determine the level of ability to write narrative descriptions, the components of narrative writing that have not been mastered by students include orientation, complications, evaluation (if any), resolution, code, linguistics of narrative essay, and spelling. This research data collection was carried out using a narrative writing test using the Storybird media. Based on the results of calculations and data analysis, two results were obtained from this study. First, the ability to write narratives of personal experiences of PBSI USD students using Storybird is in the medium category with an average of 5,33, the standard deviation of 1.94, and is in the score interval of 4.36-6.2. Second, there are two narrative components that need to be improved in creative writing training, especially in narrative writing. The two components include the structure of the narrative text and linguistic components at the phonological, morphology, syntax, and spelling levels.